Atribut Umum Versus Atribut Islami; Manakah Yang Paling Berpengaruh Bagi Wisatawan Muslim? - Mashilal Mashilal; Ramadhan Dwi Swasana (ITB AAS INDONESIA Surakarta, 2023)
Attributes of destinations are important elements of attraction for tourists. Attributes of destinations affect tourist satisfaction. The purpose of this study was to examine the effect of generic and Islamic attributes on tourist loyalty through tourist satisfaction as an intervening variable. This type of research is quantitative research. Analysis of the model used is Partial Least Square-Structural Equation Modeling (PLS-SEM). The data in this study are primary data with 194 Muslim tourist respondents in Central Java. The sampling technique was carried out using purposive sampling method. The results of this study indicate that there is a positive and significant influence of generic attributes and Islamic attributes on tourist satisfaction. The effect of generic attributes, Islamic attributes and tourist satisfaction on tourist loyalty is positive and significant. Meanwhile, the magnitude of the influence of generic attributes is stronger than Islamic attributes on the satisfaction and loyalty of Muslim tourists.